2018
DOI: 10.1007/s40744-018-0097-3
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide, 3-Year, Post-Marketing Surveillance Experience with Tofacitinib in Rheumatoid Arthritis

Abstract: Pfizer Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
61
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 15 publications
(20 reference statements)
6
61
0
1
Order By: Relevance
“…In patients with AD, a phase IIa study showed improvement of the Eczema Area and Severity Index (EASI) scores after 4 weeks of topical tofacitinib treatment . In rheumatoid arthritis, tofacitinib has been approved since 2012 and has shown minimal adverse events and good tolerance . Although the action of small molecule inhibitors, such as JAK1/3 inhibitors, is rather well understood on leucocytes, little is known about direct effects of kinase inhibitors on human keratinocyte function and skin barrier formation.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with AD, a phase IIa study showed improvement of the Eczema Area and Severity Index (EASI) scores after 4 weeks of topical tofacitinib treatment . In rheumatoid arthritis, tofacitinib has been approved since 2012 and has shown minimal adverse events and good tolerance . Although the action of small molecule inhibitors, such as JAK1/3 inhibitors, is rather well understood on leucocytes, little is known about direct effects of kinase inhibitors on human keratinocyte function and skin barrier formation.…”
Section: Introductionmentioning
confidence: 99%
“…5 Further, recent post-marketing surveillance experience has revealed two cases of histoplasmosis in patients on tofacitinib occurring in endemic regions. 6 To our knowledge, this is the first case of phaeohyphomycosis with tofacitinib and adds to the growing literature of mycoses related to the use of Janus-kinase inhibitors.…”
Section: Tofacitinib: Raising Awareness Of Mycosesmentioning
confidence: 61%
“…In an integrated safety analysis of 6194 patients on tofacitinib, out of 61 cases of opportunistic infection, there were 12 cases of oesophageal candidiasis, 5 cases of pneumocystosis and 5 cases of cryptococcal infection . Further, recent post‐marketing surveillance experience has revealed two cases of histoplasmosis in patients on tofacitinib occurring in endemic regions . To our knowledge, this is the first case of phaeohyphomycosis with tofacitinib and adds to the growing literature of mycoses related to the use of Janus‐kinase inhibitors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by the presence of autoantibodies and erosive synovitis that mainly involves small joints (1). Tofacitinib is the first oral Janus Kinase (JAK) inhibitor approved in 2012 for the treatment of patients with active, moderate to severe RA that does not respond to other therapies (2). Objectives: The objective was to describe demographic and clinical results of a cohort of Colombian patients with RA treated with tofacitinib.…”
mentioning
confidence: 99%